Outcomes of cancer survivorship education and training for primary care providers: a systematic review - Chan, Raymond J.; Agbejule, Oluwaseyifunmi Andi; Yates, Patsy M.; Emery, Jon; Jefford, Michael; Koczwara, Bogda; Hart, Nicolas H.; Crichton, Megan; Nekhlyudov, Larissa (Journal of cancer survivorship, 2022)
Purpose To identify published literature regarding cancer survivorship education programs for primary care providers (PCPs) and assess their outcomes. Methods PubMed, Embase, and CINAHL databases were searched between January 2005 and September 2020. The Quality of Cancer Survivorship Care Framework and Kirkpatrick’s 4-level evaluation model were used to summarize program content and outcomes, respectively. Data extraction and critical appraisal were conducted by two authors. Results Twenty-one studies were included, describing self-directed online courses ( n =4), presentations ( n =2), workshops and training sessions ( n =6), placement programs ( n =3), a live webinar, a fellowship program, a referral program, a survivorship conference, a dual in-person workshop and webinar, and an in-person seminar and online webinar series. Eight studies described the use of a learner framework or theory to guide program development. All 21 programs were generally beneficial to PCP learners (e.g., increased confidence, knowledge, behavior change); however, methodological bias suggests caution in accepting claims. Three studies reported positive outcomes at the patient level (i.e., satisfaction with care) and organizational level (i.e., increased screening referrals, changes to institution practice standards). Conclusions A range of cancer survivorship PCP education programs exist. Evidence for clinical effectiveness was rarely reported. Future educational programs should be tailored to PCPs, utilize an evidence-based survivorship framework, and evaluate patient- and system-level outcomes. Implications for Cancer Survivors PCPs have an important role in addressing the diverse health care needs of cancer survivors. Improving the content, approach, and evaluation of PCP-focused cancer survivorship education programs could have a positive impact on health outcomes among cancer survivors.